Economic Benefits of Marine Protected Areas, Case of Anambas Islands, Indonesia - Leny Dwihastuty; Supriyadi Supriyadi; Umi Muawanah; Muhammad H. Jayawiguna (Jurnal Segara, 2022)
This study aims to evaluate the economic benefits derived from conservation areas using the case of National Marine Protected Areas (MPA) in Anambas Islands. The study evaluated the top four reef-associated fish with high economic values, namely grouper, red snapper, threadfin bream, and trevally fish.  The employed bioeconomic hybrid model to estimate the Maximum Economic Yield (MEY) for those fish under the sustainable conservation policies. We found positive economic benefits from conservation in Anambas Islands. The MPA has shown both biological and economic benefits, namely the spill over impact and total economic value of harvest at amount of IDR 301,481,685,170/year. We found that the 50% MSY policy on fisheries TAC in MPA site will still sustain the fisheries resource but fishers are less profitable. Some strategies to augment the outcome of Anambas Islands MPA include affirmation policies both from national and local government to increase fishing capacity and skills such as operating larger vessels, eg 10 GT and provide programs and assistance on providing alternative livelihoods for fishermen.